Histiocytoid Sweet Syndrome Is More Frequently Associated With Myelodysplastic Syndromes Than the Classical Neutrophilic Variant: A Comparative Series of 62 Patients. Issue 15 (April 2016) - Ghoufi, Lisa; Ortonne, Nicolas; Ingen-Housz-Oro, Saskia; Barhoumi, Walid; Begon, Edouard; Haioun, Corinne; Pautas, Cécile; Beckerich, Florence; Robin, Christine; Wolkenstein, Pierre; Cordonnier, Catherine; Chosidow, Olivier; et al.
Abstract : Abstract: Histiocytoid Sweet syndrome (H-SS) is a histological variant of Sweet syndrome (SS) differing from classical neutrophilic SS (N-SS) by a dermal infiltrate mainly composed of lymphocytes and histiocytoid myeloperoxidase-positive cells. We aimed to report a large series of H-SS and compare the frequency and type of hematological malignancies associated to H-SS and N-SS. We included 62 patients with a coding histopathologic diagnosis of SS prospectively registered between 2005 and 2014 in the database of our Department of Pathology. Overall, 22 (35.5%) and 40 (64.5%) patients had a histological diagnosis of H-SS and N-SS, respectively. Median age, sex ratio, and cutaneous lesions were similar in the 2 groups. The frequency of extra-cutaneous manifestations was similar (50% vs 37.5%, P  = 0.42). Recurrent forms were significantly more frequent in H-SS than in N-SS patients (21% vs 2.5%, P  = 0.01). A hematological malignancy was diagnosed in 22 patients, 12 (55.5%) with H-SS and 10 (25%) with N-SS ( P  = 0 .019). Hematological malignancy was of myeloid origin in 8/22 (36.3%) H-SS and 5/40 (12.5%) N-SS patients ( P  = 0 .02), and of lymphoid origin without myeloid component in 4/22 (18.1%) H-SS and 4/40 (10%) N-SS patients ( P  = 0 .35), respectively. One N-SS patient had a hematological malignancy of mixed (myeloid and lymphoid) phenotype. A myelodysplastic syndrome (MDS) was diagnosed in 7/22 (31.8%) H-SS and 1/40 (2.5%) N-SS patients ( P  < 0 .001). Hematological disease was diagnosed before (in 8 H-SS and 3 N-SS patients) or at the time of the occurrence of the cutaneous lesions (in 1 H-SS and 7 N-SS patients). However, in 3 H-SS patients, all with MDS, cutaneous lesions preceded the hematological disease by ≤6 months. In conclusion, H-SS was associated with MDS in one third of patients but also with lymphoid malignancies, and cutaneous lesions could precede the hematological diagnosis in patients with MDS. A complete hematological assessment is mandatory at diagnosis, and monitoring blood cell counts should be recommended for at least 6 months after the diagnosis of H-SS.